MANAJEMEN KELEMBAGAAN BERBASIS ETIKA BUDDHA - Sapardi Sapardi (Jurnal Ilmiah Kampus: Sati Sampajanna, 2019)
The precepts/morals ethics that Buddha taught are very relevant to the current situation of theglobalization era. Behaving morally is a condition of self-internalization and strict safeguarding thevirtues and not harming others. Therefore, the precepts become the basis in creating patterns of socialinstitutional management in dealing with various conditions of changes in the modern era faced by theworld community. The institutional world will become safe and peaceful with the presence ofInstitutional Management Based on Buddhist Ethics.In analyzing and dissecting the data of the text referred to using the theory of structuralfunctionalism, hermeneutics, and paticcasamuppada so that it is expected to get a clear understandingto reveal the Institutional Management Based on Buddhist Ethics. It can be seen that based on dataanalysis the texts refer to the pattern of institutional management in forming a harmonious systemand therefore there are conditions that are interrelated to one another. Institutional ManagementBased on Buddhist Ethics is the basis and guide in creating a managerial system that is Buddhist.Institutional management will function properly and correctly on the basis of the behavior of eachindividual in it which is operationally guided by Buddhist morals.90This research was conducted to find out how Institutional Management Based on BuddhistEthics. It is also related to find out the relationship and the interrelationship of the themes of Buddhistteachings in the management of social institutions related to their application. Research data obtainedfrom the identification of texts from the Tipitaka/Tripitaka Scriptures related to institutionalmanagement.